1975
DOI: 10.1212/wnl.25.12.1149
|View full text |Cite
|
Sign up to set email alerts
|

Disconnection of the cerebral hemispheres

Abstract: A boy with intractable siezures that had progressed to about 30 a day underwent complete disconnection of the cerebral hemispheres in January 1972. Using microsurgical technique, we followed the path described by Bogen and Vogel requiring division of the corpus callosum from rostrum to splenium, the anterior commisure, one fornix, and hippocampal commissure. Postoperative recovery was complicated by aseptic meningitis, which was treated with dexamethasone and, later by hydrocephalus, which was reduced by ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(17 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…The left and right HPCs are directly connected by the hippocampal commissure (Wilson, Culver, Waddington, & Gazzaniga, 1975), and their activities show definite synchronization (Goto et al, 2010). Consistently, all the subjects enrolled in this study showed significant correlations between the left and right HPCs in terms of the BOLD signal changes with time in resting-state functional MRI.…”
Section: Discussionsupporting
confidence: 82%
“…The left and right HPCs are directly connected by the hippocampal commissure (Wilson, Culver, Waddington, & Gazzaniga, 1975), and their activities show definite synchronization (Goto et al, 2010). Consistently, all the subjects enrolled in this study showed significant correlations between the left and right HPCs in terms of the BOLD signal changes with time in resting-state functional MRI.…”
Section: Discussionsupporting
confidence: 82%
“…In the early 1960s, Bogen reported a small series of similarly operated patients with encouraging results [12,13,14], and Luessenhop described comparable success in three of four children [123,124]. In 1971, Wilson chose this procedure as an alternative to hemispherectomy in a 9-year-old boy with infantile hemiplegia and began compiling a series of 20 patients that ultimately revealed the efficacy of the procedure, warranting its wider application [74,169,271,272,273,274,275].…”
Section: Callosotomymentioning
confidence: 99%
“…They divided the corpus callosum as well as the anterior commissure, massa intermedia, and one fornix. With the introduction of microsurgical technique the pro cedure has been refined, with concomitant reductions in morbidity and mortality [2][3][4][5][6]. Corpus callosotomy is now a safe and effective treatment for patients with intractable epilepsy, particularly for those susceptible to injury from drop attacks [7].…”
Section: Introductionmentioning
confidence: 99%